High SEC61A1 expression predicts poor outcome of acute myeloid leukemia - Ji Guo; Yang Xiaofei; Li Jun (Open Medicine, 2024)
The malfunction of SEC61A1 has been linked to several types of cancers, but its role in acute myeloid leukemia (AML) remains poorly understood. In this study, we used a series of bioinformatics analysis techniques, including gene expression profiling and proteomic analysis. Our findings were subsequently validated through a series of in vitro experiments, such as SEC61A1 knockdown in cell lines and RT-qPCR. We discovered a significant up-regulation of SEC61A1 in AML patients compared to healthy controls. AML patients with elevated SEC61A1 expression exhibited reduced overall survival compared to those with lower expression. Moreover, SEC61A1 expression emerged as an independent risk factor for predicting the survival of AML patients undergoing allo-HSCT. Our analysis also revealed an association between high SEC61A1 expression and increased signaling pathways related to cell growth. Our study underscores the importance of SEC61A1 expression as a novel prognostic indicator for predicting survival among AML patients, while also identifying it as a promising therapeutic target.